Effect of Aging on Short Term Heart Rate Variability - Akhter, Qazi Farzana; Akhter, Qazi Shamima; Rohman, Farhana; Sinha, Susmita; Ferdousi, Sybilla (Journal of Bangladesh Society of Physiologist, 2015)
Background: Heart rate variability has been considered as an indicator of autonomic nerve function status. Few works have been done to assess the heart rate variability in normal healthy subjects in different countries. Objectives: To assess the cardiac autonomic nerve function status in healthy Bangladeshi population of different age groups by analyzing time domain measures of Heart Rate Variability. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from the period of July 2012 to June 2013. For this purpose, a total number of 180 healthy subjects were selected with the age ranging from 15-60 years of both sexes. All the study subjects were divided into 3 different groups according to age (Control 15-30 years; middle age 31-45 years; older age 46-60 years). Each group included 60 subjects of which 30 were male and 30 were female. The subjects were selected from different areas of Dhaka city by personal contacts. HRV parameters were recorded by a 4 active channels, RMS Polyrite-D-2 machine For statistical analysis, one way ANOVA, unpaired Students t-test and Pearsons correlation coefficient test were performed. as applicable. Results: Systolic blood pressure (SBP), diastolic blood pressure (DBP) were significantly (p<0.001) higher in older group in comparison to control & middle age group. Again RR interval and RMSSD (p<0.001), were significantly lower in older age group (p<0.05) compared to control & also to middle age group. But HR was found significantly higher (p<0.05)in both middle and older subjects than control and also in older (p<0.05) compared to middle age. Correlation analysis showed moderate negative correlation of mean R-R with age in middle age whereas significant negative correlation for RMSSD both in middle and older age subjects. Conclusion: In this study, markedly decreased cardiac parasympathetic function were found with aging process. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22801 Bangladesh Soc Physiol. 2014, December; 9(2): 78-82